Las smart cities o transformación digital de las ciudades en Colombia: Estado del arte - Pereira, Milton; Molina, Emilio; Londoño, Sergio (Pontificia Universidad Católica del Perú, 2025)
This paper addresses the concept of smart cities and reviews the state of the art in Colombia in terms of standards, policies and guidelines on smart cities, digital government, and digital transformation that the Republic of Colombia has adopted. Currently there is no normative document that seeks to intertwine the system of cities as a land use planning policy and smart cities policies, which in our view have a necessary and indissoluble relationship. When these policies act in a disjointed manner, in the authors’ opinion, it is not possible to speak of smart cities, but rather the beginning of policies for the digital transformation of cities. A smart city cannot be limited only to ICTs and their access but is smart to the extent that it seeks to include ICTs in land use planning processes and land management instruments for the purpose of improving the quality of life and the efficiency of the operation of urban services. The guidelines for the implementation of ICTs in cities that do not incorporate land use planning strategies and urban policies is not properly the development of a Smart Cities model but a process of digital transformation of the territories.

Este trabajo aborda el concepto de ciudades inteligentes y hace una revisión sobre el estado del arte en Colombia en cuanto a las normas, políticas y lineamientos que, en materia de ciudades inteligentes, gobierno y transformación digitales ha adoptado la República de Colombia. En la actualidad no existe un documento normativo que pretenda entrelazar el sistema de ciudades como política de ordenamiento territorial y las políticas de ciudades inteligentes, las cuales, a nuestro modo de ver, tienen una relación necesaria e indisoluble. Cuando esas políticas actúan de manera desarticulada a criterio de los autores, no es posible hablar de ciudades inteligentes, sino el inicio de políticas de transformación digital de las ciudades. Una ciudad inteligente no se puede limitar únicamente a las TIC y a su acceso, sino que es inteligente en la medida que pretende incluir, en los procesos de ordenamiento territorial y en sus instrumentos de gestión de suelos, a las TIC para efectos de mejorar la calidad de vida y la eficiencia de la operación de los servicios urbanos. Los lineamientos para implementación de TIC en las ciudades que no incorporen estrategias de ordenamiento territorial y políticas urbanísticas no es propiamente el desarrollo de un modelo de Smart Cities, sino un proceso de transformación digital de los territorios.
Smart cities or the digital transformation of cities in Colombia: state of the art
Keywords: Smart Cities; Digital transformation of Cities; City; Land Use Planning; Urban Planning; Smart Cities; Transformación Digital de las Ciudades; Ciudad; Ordenamiento; Territorial; Urbanismo; https://purl.org/pe-repo/ocde/ford#5.06.00